PERANCANGAN SISTEM INFORMASI PEMBAYARAN IURAN RW BERBASIS WEBSITE PADA PERUMAHAN NURI BINTARO - AHMAD RIDHO, RIDHO (2023)
In an effort to improve the efficiency of using technology and information in managing citizen administration, managing citizen contribution data, and preparing monthly fee reports at Nuri Bintaro Jaya Housing, the role of a reliable system is very important. Currently, there is no system that can effectively manage citizen data, administrative data, and contribution data. All data is still recorded manually using special paper or books, which are prone to loss or damage. This often causes various problems, such as the loss of data on citizens who have not paid dues in the previous month or poor storage, so that the data and needs received by the management each month are not properly met. In addition, the grouping of citizen data is also still done manually, which takes quite a long time. In this study, the design of an information system for payment of RW fees was carried out using the prototyping method and PIECES analysis which was chosen because of its flexibility. This system is designed using the programming language HTML, PHP, and MySQL database. The results of this study are web-based RW fee payment applications, which make it easier for admins to manage data, make it easier for residents to pay monthly fees, and make it easier to print reports.